Three dimensional finite element analysis of mandibular premolar restored with fiber post and resin composite with different cavity designs - Daraporn Sae-Lee; Teerapan Sosakul; Watcharin Hovichitr; Jarupol Suriyawanakul; Pongsakorn Poovarodom; Wiphatpong Bumrungsiri; Somchai Pongkornkumpon; Wachira Supasatean (KKU Engineering Journal, 2016)
The investigation of the stress distribution and fatigue lifetime of endodontically treated mandibular premolar with various cavity designs for access opening, restored by resin composite with or without a fiber post was performed. A 3D model of a mandibular premolar with one root canal was selected. The 11 study models of tooth structure including enamel, dentine and pulp tissue were generated with different cavity designs, i.e., Class I, Class II OM, Class II MOD, Class V, Class V pulp exposure, cortical and cancellous bone, root canal configuration, as well as fiber post. A load of 150 Newtons was applied on the lingual incline plane of the buccal cusp at an angle of 45 degrees to the long axis of the tooth. The results show that the stress distributions in all models were similar, i.e., the maximum von Mises stresses were observed at the level of the cement-enamel junction (CEJ), and the stress decreased abruptly from the outer to the inner part of the tooth. The maximum von Mises stress along the tooth axis was concentrated at the load-bearing areas, and decreased gradually from the coronal region to the apex of the root. The fatigue lifetimes of the models restored with a fiber post were greater than those without a fiber post.